2018
DOI: 10.1029/2018gl079621
|View full text |Cite
|
Sign up to set email alerts
|

Snowpack Change From 1982 to 2016 Over Conterminous United States

Abstract: Snow water equivalent (SWE) variability and its drivers over different regions remain uncertain due to lack of representativeness of point measurements and deficiencies of existing coarse‐resolution SWE products. Here, for the first time, we quantify and understand the snowpack change from 1982 to 2016 over conterminous United States at 4‐km pixels. Annual maximum SWE decreased significantly (p < 0.05) by 41% on average for 13% of snowy pixels over western United States. Snow season was shortened significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
130
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(153 citation statements)
references
References 34 publications
(63 reference statements)
2
130
1
Order By: Relevance
“…Following previous studies (Mote, 2006;Zeng et al, 2018), we partitioned the entire CONUS into two geographic units (Western and Eastern CONUS) using the 100°W longitude line for discussion. We resized this data set from 4-km to 0.125°spatial resolution to match the model grids using the nearest neighbor interpolation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following previous studies (Mote, 2006;Zeng et al, 2018), we partitioned the entire CONUS into two geographic units (Western and Eastern CONUS) using the 100°W longitude line for discussion. We resized this data set from 4-km to 0.125°spatial resolution to match the model grids using the nearest neighbor interpolation.…”
Section: Resultsmentioning
confidence: 99%
“…We resized this data set from 4-km to 0.125°spatial resolution to match the model grids using the nearest neighbor interpolation. Following previous studies (Mote, 2006;Zeng et al, 2018), we partitioned the entire CONUS into two geographic units (Western and Eastern CONUS) using the 100°W longitude line for discussion. While we are aware that more detailed data analyses through aggregation by latitude may generate some extra insights on the climatic impacts (e.g., Saavedra et al, 2018), in this study, we aggregate the data by relative humidity and elevation (related to humidity) to focus on the effects of humidity on precipitation phase prediction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to real‐time snow observations, a long‐term record of SWE is important for identifying climate variability and trends and for developing a climatology of the snowpack. As changes in seasonal snow have recently accelerated across the United States in the last few decades (Ashfaq et al, ; Georgakakos et al, ), reliable long‐term SWE measurements are further needed for effective water management and flood risk assessments (Zeng et al, ). Point‐based long‐term SWE records from snow station networks (e.g., NRCS Snowpack Telemetry [SNOTEL]) have provided high‐quality measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Over 60 million people in the western United States are reliant on snowmelt runoff for consumption, electrical power, and agriculture (Bales et al, 2006). Declines in mountain snowpack storage (Mote, 2003(Mote, , 2006Mote et al, 2005Mote et al, , 2018Zeng et al, 2018), earlier spring snowmelt (Clow, 2010;Harpold et al, 2012;McCabe & Clark, 2005;Regonda et al, 2005;Stewart et al, 2005), and slower snowmelt rates (Harpold & Kohler, 2017;Wu et al, 2018) have been reported in the western United States, all of which are related to a warming climate (Barnett et al, 2005;Hamlet et al, 2005;Kapnick & Hall, 2012;Mote et al, 2018).…”
Section: Introductionmentioning
confidence: 99%